Polycystic ovary syndrome (PCOS) and kisspeptin - A Sri Lankan study - Umayal, B; Jayakody, S; Chandrasekharan, N; Wijesundera, W; Wijeyaratne, C (Journal of postgraduate medicine, 2019)
Context: Polycystic ovary syndrome (PCOS) is the commonest endocrine disorder affecting young women. Kisspeptins are a family of closely related peptides encoded by Kiss1 gene that controls the hypothalamic-pituitary-gonadal axis by binding to its receptor (GPR54) expressed in gonadotropin-releasing hormone (GnRH) neurons and releases GnRH. Since GnRH secretion is deregulated in PCOS, we hypothesized that dysregulated gonadotropin secretion in PCOS is reflected by kisspeptin levels. Aim: We aimed to measure serum kisspeptin levels of subjects with well-characterized PCOS versus controls and explore any correlation between kisspeptin and PCOS-related reproductive and metabolic disturbances. Materials and Methods: Consecutive women with PCOS manifesting from adolescence (n = 55) and adult controls (n = 110) were recruited. Pre-treatment baseline clinical, anthropometry, and biochemical parameters were measured in all. Serum kisspeptin and testosterone levels were determined by enzyme-linked immunosorbent assay method. Results: Serum kisspeptin and testosterone concentrations were significantly higher in women with PCOS (kisspeptin 4.873 nmol/L; testosterone 4.713 nmol/L) than controls (kisspeptin 4.127 nmol/L; testosterone 3.415 nmol/L; P < 0.05). Serum kisspeptin levels were positively associated with PCOS (odds ratio: 1.853; 95% confidence interval: 1.246-2.755; P = 0.002) in our studied population. Conclusion: Serum kisspeptin levels are higher in Sri Lankan women with PCOS manifesting from adolescence compared with controls regardless of body mass index. We propose serum kisspeptin concentration as a useful marker to recognize PCOS that manifests from adolescence.